2018
DOI: 10.1002/mnfr.201800027
|View full text |Cite
|
Sign up to set email alerts
|

Theobromine Does Not Affect Fasting and Postprandial HDL Cholesterol Efflux Capacity, While It Decreases Fasting miR‐92a Levels in Humans

Abstract: ScopeChocolate consumption lowers cardiovascular disease risk, which might be attributed to the methylxanthine theobromine. These effects may be mediated through effects on HDL‐mediated cholesterol efflux, which may be affected by microRNA (miRNA) levels in the HDL particles. Therefore, the aim of this study is to investigate effects of theobromine consumption on fasting and postprandial cholesterol efflux and miRNAs levels.Methods and resultsThirty overweight and 14 obese healthy men and women participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
(122 reference statements)
1
13
0
Order By: Relevance
“…Although not evaluated in their circulating form, a recent study carried out with peripheral blood mononuclear cells showed that diets enriched in saturated fatty acids modify miRNA expression [23], suggesting that postprandial lipemia also influences miRNA expression in tissues. In contrast to previous studies, where specific c-miRNAs were evaluated in a postprandial state [24,25], our data evaluate the whole mice miRNome for the first time. Figure 2B–D shows the differential miRNA expression between different genotypes in mice.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although not evaluated in their circulating form, a recent study carried out with peripheral blood mononuclear cells showed that diets enriched in saturated fatty acids modify miRNA expression [23], suggesting that postprandial lipemia also influences miRNA expression in tissues. In contrast to previous studies, where specific c-miRNAs were evaluated in a postprandial state [24,25], our data evaluate the whole mice miRNome for the first time. Figure 2B–D shows the differential miRNA expression between different genotypes in mice.…”
Section: Resultsmentioning
confidence: 97%
“…However, there is scarce information about the levels of circulating miRNAs in response to postprandial dietary fat challenge. While one study in the rainbow trout fish showed that circulating miRNAs-128 and miR-223 are subjected to postprandial regulation and might reflect cholesterol-based changes in the liver [24], another study in humans reported an increase of miR-92a and miR-223 in ApoB-depleted serum after consumption of a high-fat meal [25]. These two studies evaluated specific miRNAs; however, there is very little information about postprandial c-miRNAs at a larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we summarize the evidence on HDL functionality (CEC, CETP activity, and its antioxidant capacity by PON1 activity) as well as its expression and relationship with functional foods (extra virgin olive oil [ 27 , 81 , 83 , 84 , 85 ], whole grains [ 81 ], nuts [ 27 , 81 , 86 , 87 ], legumes [ 81 , 88 ], fresh fish [ 81 , 89 , 90 ], red wine [ 91 ]), fruits and vegetables [ 92 , 93 , 94 , 95 ], ginger [ 80 ], green tea [ 91 , 96 ], cocoa [ 91 , 97 ], and bioactive compounds as curcumin [ 79 , 80 ], resveratrol [ 78 , 98 ], and quercetin [ 75 , 76 , 99 ].…”
Section: Dietary Compounds and Their Effects On The Modulation Of Hdl-c Functionalitymentioning
confidence: 99%
“…There is evidence in the literature of functional foods and/or bioactive substances related to CEC, such as extra virgin olive oil [ 27 , 81 , 83 , 84 ], fruits [ 92 , 93 ], nuts [ 87 ], legumes [ 88 ], fish [ 89 , 90 ], quercetin [ 75 , 76 ], green tea, cocoa [ 91 , 97 ], red wine [ 91 ], curcumin [ 79 ], and resveratrol [ 78 ] ( Table 1 ).…”
Section: Dietary Compounds and Their Effects On The Modulation Of Hdl-c Functionalitymentioning
confidence: 99%
“…Apart from its nutrients, pleasant flavor, aroma, and color, cocoa is also known for offering many health benefits (Bonvehí, 2005), because it is an excellent source of antioxidants (Langer, Marshall, Day, & Morgan, 2011). Many different bioactive compounds are present in cocoa, such as polyphenols, mainly flavonoids (flavanols, procyanidins, and anthocyanins), and methylxanthines (caffeine and theobromine; Talbot, Mensink, Smolders, Bakeroot, & Plat, 2018), among others. These phytochemicals can be present at different concentrations depending on diverse factors like cocoa variety and cocoa processing, which can lead to the presence of new bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%